A mathematical model for pressure drop of two-phase dry-plug flow in circular mini/micro channels. (December 2016) - Heravi, Pooyan; Torabi, Farschad
Highlights: Flaws found in previous pressure drop model of two-phase dry-plug flow regime are discussed. A new model for two-phase dry-plug flow regime is proposed. The new model is capable of accurate pressure drop prediction for the available experimental data./ Based on assumptions, the model should be applicable and accurate for a wide range of Ca numbers and contact angles. Abstract: Dry-plug flow is a variation of two-phase plug flow that occurs in small scale channels and refers to the dry wall conditions at gas portions of the flow regime. Previous experimental studies found a significant increase in pressure drop in this flow regime from the two-phase wet-plug flow regime. In this work an analytical model for the pressure drop of this flow regime is developed and phenomena that influence pressure drop are examined. Unlike previous models, the proposed model seems to be applicable to a wide range of capillary numbers and give good estimations for all static contact angles. Contact angle hysteresis turned out to play a major role in inducing pressure drop in this flow regime. Model's predictions were in good agreement with previous experimental data. Finally the model is applied to very low capillary number region and pressure drop predictions for this region are presented.